Rebels with a cause - Patterson, James; Grabenstein, Chris; Jahnson, Beverly (London Young Arrow, 2020)
Max and her CMI friends attempt to use their smarts to find solutions to a water crisis, while a greedy corporation with an eye on capturing Max seems to know their every move
Authers of the No. 1 New York times bestseller Max Einstein : the genius experiment
English stories
Keywords: Action and adventure fiction; English stories